Production of antimicrobial chitosan nanoparticles against food pathogens - Madureira, Ana Raquel (2016)
Chitosan nanoparticles (NPs) may be a promissory delivery system of polyphenols. The main objective of this study was to produce chitosan NPs encapsulated with polyphenols with antimicrobial and antioxidant activity against food pathogens. The NPs produced with low and high molecular weight chitosan (LMWC and HMWC) were successfully obtained showing slight variations in the particle size, in the range 300-600 nm, and zeta potential values in the range 20-30 mV, exhibiting a moderate stability. The best encapsulation performance was obtained for NPs produced with LMWC and the polyphenol rosmarinic acid. The antimicrobial studies proved that all free and encapsulated compounds have inhibitory activity upon the tested bacteria (Bacillus cereus, Escherichia coli O157, Listeria innocua, Staphylococcus aureus, Salmonella typhimurium and Yersinia enterocolitica). The images obtained by electronic microscopy showed that it was possible to obtain NPs capable of affecting the cellular structure of bacteria reinforcing their antimicrobial activity.